Opioids, adjuvants, and interventional options for pain management of symptomatic metastases - Ghosh, Amrita; Berger, Ann (Annals of Palliative Medicine; Vol 3, No 3 (July 18, 2014): Annals of Palliative Medicine (Multidisciplinary Approaches to Palliation for Advanced and Metastatic Malignancies), 2014)
Cancer pain is a complex issue that unfortunately affects a majority of cancer patients, the assessment and treatment of which are equally essential in alleviating many facets of this pain. The objective of this section is to address the many facets of cancer pain: its assessment, management, and its varied treatment modalities. We will discuss characteristics of pain, essential aspects of the patient interview, and management using opioids, adjuvants, and interventional and invasive strategies as well as side effects of these techniques. Many of these modalities are used for palliation but may and should be used in cancer patients who experience side effects from both their cancer and their chemotherapeutics.